Urban Archaeology and Heritage as a Part of Contemporary City Planning and Identity Building - Seppänen Liisa (Suomen arkeologinen seura, 2022)
This article discusses the role of archaeological excavations and research in urban planning, development projects and the contemporary townscape of Finland. Using the examples of two Finnish towns, this article demonstrates how archaeological and cultural heritage are represented in urban townscapes today, as a part of their history and city building. One of the towns, Turku, is the oldest town of Finland, with a long history of urban archaeology. The other town, Lahti, was established in the late 19th century and was the site of archaeological excavations in the 1990s and 2010s.
The author reflects on the work of the last few decades and makes some overtures about developing collaboration and on-going dialogue among urban archaeology, city planning and urban development. No matter what the nature of collaboration among these parties is, it certainly has a great impact on a city’s environment and the formation of its identity. Furthermore, it also affects how people living in and visiting the city feel and experience it as well as how their awareness of the city’s past is inculcated and supported.
Landscapes of the Past and Future: Current Finnish Research in Landscape Archaeology